Treatment with epoprostenol reverts nitric oxide non-responsiveness in patients with primary pulmonary hypertension. Issue 4 (1st April 2000) - Ziesche, R; Petkov, V; Wittmann, K; Kopatschka, J; Stiebellehner, L; Schenk, P; Germann, P; Röder, G; Ullrich, R; Block, L H
Abstract : OBJECTIVE: To assess whether long term treatment with epoprostenol might restore primary non-responsiveness to nitric oxide (NO) in patients with primary pulmonary hypertension. METHODS: Seven patients with primary pulmonary hypertension receiving intravenous epoprostenol continuously because of failure of NO to influence pulmonary haemodynamics during initial testing were followed over a period of 13–29 months. Afterwards, acute vascular reactivity towards NO was tested again during right heart catheterisation. RESULTS: Administration of NO after continuous epoprostenol treatment for a mean period of 18 months improved arterial oxygen saturation (p < 0.01) and cardiac index (p < 0.05), and decreased mean pulmonary artery pressure (p < 0.01) and total pulmonary vascular resistance (p < 0.01) in patients previously unresponsive to NO. CONCLUSIONS: Long term treatment with epoprostenol reverts initial refractoriness to NO in patients with primary pulmonary hypertension. Thus the addition of NO to epoprostenol treatment might cause further improvement in the course of the disease.